IMPACT OF ABRATION ON LAND USE IN COASTAL AREA BULELENG REGENCY - Parwati, Luh Putu Gita Ari; Dwijendra, Ngakan Ketut Acwin; Agusintadewi, Ni Ketut (ASTONJADRO, 2022)
Coastal damage due to abrasion and wave erosion in Buleleng Regency is very potential, even information from the Buleleng Regency Marine Service released information that the length of the coast in Buleleng Regency which has been damaged is not less than 5 km. Abrasion and wave erosion resulting in erosion of the coastline and will continue to affect land use. In this study using quantitative methods with analysis stages consisting of, among others, land use and analysis of the impact of abrasion on land use. The analysis carried out is a Geographic Information System (GIS) based analysis in accordance with the needs of the research in spatial terms. The conclusions obtained from this study are the types of land use that exist in the Coastal District of Buleleng Regency are in the form of airports, lakes / reservoirs, forests, mangroves, stretches of beach sand, ports, plantations / gardens, paddy fields, rivers, moor and shrubs. The abrasion that occurs in the Coastal Zone of Buleleng Regency every year with vulnerability during 2013 - 2019 has an impact on land use changes. This can be seen through the results of overlapping overlay analysis and seeing the area of land use that has changed.